Localized lymphatic sporotrichosis after fish-induced injury (Tilapia sp.) - Haddad, V; Miot, Hélio Amante [UNESP]; Bartoli, L. D.; Cardoso, A. D.; De Camargo, RMP (B I O S Scientific Publishers Ltd, 2002)
Localized lymphatic sporotrichosis generally develops after the fungus Sporothrix schenckii is traumatically introduced into skin or mucosa by contaminated plant material. An 18-year-old male fisherman was injured by spines of the dorsal fin of a fish on the left third finger. The lesion became ulcerated, edematous and suppurative and did not respond to tetracycline and cephalexin. Fifteen days after the accident, a nodular lymphangitic pattern of swelling was observed. Histopathological findings and an intradermal test were suggestive of sporotrichosis and mycological cultures confirmed the diagnosis. The lesions resolved after oral treatment with potassium iodide. Sporotrichosis is a common subcutaneous mycosis in Brazil, and there is a previous report in the literature of this disease being acquired via trauma involving fish spines.
Keywords: dermatomycosis; fish; mycosis; sporotrichosis